Increased expressions of CD123, CD63, CD203c, and Fc epsilon receptor I on blood leukocytes of allergic asthma - Xie, Hua; Chen, Liping; Zhang, Huiyun; Wang, Junling; Zang, Yanyan; Zhan, Mengmeng; Gu, Fangqiu; Wang, Shunlan; He, Shaoheng (Frontiers in Molecular Biosciences, 2022)
Abstract Background: Altered basophil identification markers have been discovered to associate with allergic asthma (AA) in recent years. However, little is known of expression of basophil markers in blood granulocytes. Aim: To parallel test blood basophils in PBMC and granulocyte populations of patients with AA and AA combined with allergic rhinitis (ARA). Methods: The expressions of surface molecules were determined by flow-cytometry. CD123 expressing cells in blood were isolated by cell sorting technique, and mouse AA models were employed for in vivo study. Results: The numbers of CD123+HLA-DR- cells in granulocytes of AA and ARA patients markedly increased. However, only 49.7% CD123+HLA-DR- cells in granulocytes, and 99.0% CD123+HLA-DR- cells in PBMC were basophils. Almost all CD123+HLA-DR- cells expressed CD63 regardless in granulocytes or PBMC. The numbers of CD63, FcRI and CD203c expressing cells markedly enhanced in CD123+HLA-DR- granulocytes of AA and ARA patients. Mean fluorescence intensity (MFI) of CD63 and CD203c expressions on CD123+HLA-DR- PBMC and granulocytes of AA and ARA patients dramatically elevated. House dust mite extract (HDME) and artemisia sieversiana wild allergen extract (ASWE) enhanced the numbers of CD63+CD123+HLA-DR- granulocytes and PBMC, and MFI of CD203c expression on CD123+HLA-DR- granulocyte of AA and ARA patients. Histamine, tryptase and PGD2 enhanced proportions of CD123+ KU812 cells. ASWE- and HDME-induced AA mice showed upregulated CD63 expression on basophils. In conclusion, upregulated expressions of CD123, CD203c, CD63 and FcεRIα in PBMC and granulocytes of patients with AA and ARA indicate CD123+HLA-DR- cells are involved in the pathogenesis of AA and ARA.